Substâncias antioxidantes do plasma aparentemente não influenciam a ocorrência de radiodermatite - Munhoz, Guilherme Costa; Viani Arruda, Gustavo; Maris Madeira Lana Soares, Marcela; Guttmann Batista, Dayanne; Chies, Agnaldo Bruno (Scientia Medica, 2020)
AIMS: Radiation affects not only tumors but also healthy tissues through the increment of oxidative stress. Thus, this study aimed to evaluate the oxidative stress degree as well as non-enzymatic antioxidant defenses in the plasma of patients submitted to radiotherapy and to verify if these parameters are modified in those patients who develop radiodermatitis. METHODS: Forty-one patients submitted to radiotherapy for treatment of breast cancer were followed. From these patients, plasma samples were obtained at the beginning, in the middle and at the end of the treatment, for analysis of thiobarbituric acid reactive substances (TBARS) and ferric reducing ability of plasma (FRAP). RESULTS: No significant differences were observed in terms of TBARS and FRAP in plasma harvested from these patients at the beginning and at the middle of the treatment. There was lower incidence of grade two radiodermatitis among patients undergoing radiotherapy with hypofractionated doses. There were no differences in FRAP or TBARS among patients who developed radiodermatitis of any degree in relation to those who did not develop this side effect. No differences of FRAP or TBARS were observed between patients that presented grade two radiodermatitis regarding to the others studied. CONCLUSION: There was no clear relationship between changes in TBARS or FRAP with the occurrence or severity of radiodermatitis.